Histopathological profile of sinonasal lesions with brief clinical correlation: experience in a tertiary care centre - Dr. Nehal Ahmad; Dr. Sabina Khan; Dr. M.D. Jaseem Hassan; Sujata Jetle (Tropical Journal of Pathology and Microbiology, 2017)
Background: Sinonasal lesions are a common finding in Otorhinolaryngology outpatientdepartment. Most commonly they present withnasal obstruction. Clinically many of these lesions resemble eachother but they have multiple differential diagnosis ranging from congenital, inflammatory, traumatic to neoplasticcauses that needs histopathological confirmation.Objectives: This study was undertaken to study the various histopathological patterns of sino-nasallesions, theirclassification and relative distribution of various lesions with regard to age and sex in our setting. Material and Methods: This was a retrospective study of Sino-nasal lesions specimens thatwas received at histopathology section of Department of Pathology, Hamdard Institute of Medical Science andResearch andover a period of two years from June 2014 to May 2016.Results: A total of 62 cases of sino-nasal lesions were reported during the study period. Ageranged from 5 years to 75 years with malepredominance. Among all the lesions forty five (45) were non-neoplastic, ten (10) benign and seven (7) were diagnosedas malignant tumors. Inflammatory polyp was the commonest non-neoplastic lesion while Sinonasal Papilloma was the commonest benign lesion and Sinonasal carcinoma was themost common malignancy.Conclusions: Sino-nasal lesions comprises of wide spectrum of lesions but their presenting clinicalmanifestations are very limited. Hence, on the basis of clinical picture various nonneoplastic, benign and malignantlesions may mimic each other. Histopathological diagnosis forms the mainstay of diagnosis in these lesions whichmay even reveal clinically unsuspected rare malignancies as seen in our study.